Classroom Discourse Analysis of Teacher’s Code-Switching - Fendi Ardian; Rohmani Nur Indah (LPPM Universitas Bumigora Mataram, 2022)
Classroom discourse plays a pivotal role in the conversational context at schools. The teacher as a speaking model needs to consider the speech and diction during the conversation discourse. One way to help the interaction is by employing code-switching practice since the choice of language in class discourse is essential for creating a practical and easy-to-understand class. This study aimed to find the types and functions of code-switching practiced by the English teacher. By employing a descriptive qualitative design, the data were obtained from classroom observation completed by an audio recorder based on the theory of code-switching from Poplack (1980) and Mattson & Burenhult (1999). Then, the researchers transcribed and analyzed the data into data reduction, data display, and making an inference to explore the types and the functions of code-switching practice. The participant of this study was Mrs. Zu (Pseudo), an English teacher at SMAN 2 Pare. The finding presented the types of code-switching involving inter-sentential switching, intra-sentential switching, and tag switching. The functions of code-switching cover topic switches, affective functions, and repetitive functions. The dominant practice was intra-sentential switching with affective functions during the classroom discourse. These functions help students comprehend the meaning transferred during classroom interaction.